2019
DOI: 10.1007/s11419-019-00464-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of U-47700 and its metabolites: N-desmethyl-U-47700 and N,N-didesmethyl-U-47700 in 12 autopsy blood samples employing SPE/LC–ESI-MS-MS

Abstract: Purpose The paper presents a report on the comprehensive assessment of a novel synthetic opioid (NSO) termed U-47700, and its two metabolites: N-desmethyl-U-47700 and N,N-didesmethyl-U-47700 in autopsy blood samples taken from 12 cases of fatal poisonings. Methods The analysis of the examined samples was based on the solid-phase extraction/liquid chromatography-electrospray ionization-tandem mass spectrometry method, which was developed in the validation process. In the quantitative analytical studies, deuter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…According to the background information, in most cases the deceased had a history of drug abuse. The concentrations detected in these 10 cases were similar to those reported by Mohr et al [6], Rojek et al [14] and Smith et al [15] who found median U-47,700 Among the studied cases, there was one case in which no other psychoactive substances, besides U-47,700, were detected (Case 4, Table 1). The blood concentration of U-47,700 in this case (0.27 mg/L) did not significantly differ from the median U-47,700 concentration.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…According to the background information, in most cases the deceased had a history of drug abuse. The concentrations detected in these 10 cases were similar to those reported by Mohr et al [6], Rojek et al [14] and Smith et al [15] who found median U-47,700 Among the studied cases, there was one case in which no other psychoactive substances, besides U-47,700, were detected (Case 4, Table 1). The blood concentration of U-47,700 in this case (0.27 mg/L) did not significantly differ from the median U-47,700 concentration.…”
Section: Resultssupporting
confidence: 88%
“…1), a highly selective m-receptor agonist originally developed by the company Upjohn in 1970s [3]. Since 2016, several reports have been published on serious adverse effects associated with U-47,700, including death cases [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The substance was found to be stable in all conditions. The stability of U-47700 was also confirmed by Rojek et al [7], whose fortified blood with U-47700 and its metabolites (N-desmethyl U-47700, N,N-didesmethyl U-47700) at low concentrations (25 ng/mL) and stored it at − 30 °C, + 3 °C, and + 20 °C. The analyses were performed after 1, 7, 14, and 21 days of storage.…”
Section: Discussionmentioning
confidence: 57%
“…Substances from this group pose a threat to public health in many countries, especially in Europe and the USA [2]. U-47700 has been already detected in, e.g., Belgium (2016) [3], where in 2017 it was involved in 5 deaths [4], as well as in Finland (10 deaths in 2016 and 2017) [5], Italy (2017) [6], Poland [7], the United Kingdom Supplementary Information The online version contains supplementary material available at https ://doi.org/10.1007/s1141 9-020-00568 -1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation